Muslim jurists’ opinions on the permissibility of tissue engineering experimentation: analysis of selected examples - Ahmad Radzi, Muhammad Aaʼzamuddin; Mohd. Azharuddin, Nur Syamimi; Hashi, Abdurezak Abdulahi; Noor Azmi, Azran Azhim; Sha'ban, Munirah (TERMIS, 2018)
Scientific advancement in medical and health has helped us improve the understanding in the management of human health conditions. This may be one reason Muslim jurists acknowledge the importance of evidence-based practice and thus, in principle, agreed on the permissibility of scientific research. However, they have also raised some ethical and Islamic jurisprudence concerns about the methods and implications of some biomedical practices. Despite the great discovery of cartilage tissue engineering, harm and therapeutic uncertainties spark the ethical concerns surround the technology. The stakeholders have ever since been debating on its benefits and risks. The potential applications of cartilage tissue engineering are being unveiled with much hype and expectations among the scientists and the public at large. The demand for personalized engineered tissues may increase over the time. However, the progress of cartilage tissue engineering experimentation (CTEE) has been slow due to scientific and technical challenges which related to moral, religious and philosophical aspects. The concerns involve three main components in tissue engineering (correspond to CTEE) which are the cell sources, biomaterial scaffold and stimulating factors. The discussion also included the animal study in CTEE. With the development of modern biomedical technology, Muslim jurists and ethicists raised some ethical concerns about the morality and the permissibility of applications of the technology to human body. The study employed the qualitative approach using a secondary analysis of historical documents and available contemporary materials on CTEE with regards to Islamic approach. The opinions of Muslim scholars with regards to CTEE were revealed.